Peningkatan kemampuan pemecahan masalah matematis siswa SMP kelas VIII menggunakan model discovery learning berbantuan aplikasi geogebra - Santi; Fitriani, Nelly; Setiawan, Wahyu (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2024)
This research aims to examine improving the mathematical problem solving abilities of Class VIII Middle School students using models Discovery Learning application assisted geogebra and ordinary learning models. The research method used is an experimental method with design as if experimental which involved two groups, namely the experimental class and the control class All 8th grade students in SMP Negeri 2 Cimahi became the population in this study. The samples used were class VIII-H as the experimental class and class VIII-G as the control class.  The data collection technique in this research uses instruments regarding mathematical problem solving abilities which are given twice, namely at time pretest and posttest. Data processing and analysis using applications Microsoft Excel and software SPSS 26. The results of this research show that the mathematical problem solving abilities of Class VIII Middle School students who learn using models increase Discovery Learning application assisted geogebra better than those using conventional learning.